Porównanie wartości refrakcji pooperacyjnej w stosunku do oczekiwanej u pacjentów poddanych zabiegom fakotrabekulektomii i fakoemulsyfikacji - Langwińska-Wośko, Ewa; Skopiński, Piotr; Gabrysiak-Wąsowska, Marzena; Broniek-Kowalik, Karina (Klinika Oczna / Acta Ophthalmologica Polonica, 2008)
Purpose: The aim of this study is to compare the postoperative refractive oucomes following phacotrabeculectomy and phacoemulsification with posterior chamber intraocular lens implantation. Materials and methods: The study involved the patients who underwent surgical pocedures:phacotrabeculectomy and phacoemulsification with posterior chamber intraocular lens implantation in Department of Ophthalmology Medical University of Warsaw since June 2005 to June 2006. A retrospective randomised review of postoperative refractive outcomes of 126 eyes (110 patients): 52 eyes (49 patients) that underwent phacotrabeculectomy and 74 eyes (61 patients) that underwent phacoemulsification in the same time was done. Sex and mean age was simillar in both groups of patients. We analysed the difference between preoperative predicted refractive outcome and the actual postoperative refraction. All surgery procedures were performed by two qualified optical surgeons and biometry measurements were performed by two qualified doctors. Results and conclusions: No significant difference was found between predicted errors following phacotrabeculectomy and phacoemulsification.